2020
DOI: 10.1002/elps.202000122
|View full text |Cite
|
Sign up to set email alerts
|

Determination of sulfa antibiotic residues in river and particulate matter by field‐amplified sample injection‐capillary zone electrophoresis

Abstract: In the present research, field-amplified sample injection-CZE (FASI-CZE) coupled with a diode array detector was established to determine trace level sulfa antibiotic. Sulfathiazole, sulfadiazine, sulfamethazine, sulfadimethoxine, sulfamethoxazole, and sulfisoxazole were selected as analytes for the experiments. The background electrolyte solution consisted of 70.0 mmol/L borax and 60.0 mmol/L boric acid (including 10% methanol, pH 9.1). The plug was 2.5 mmol/L borax, which was injected into the capillary at a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…With the influence of temperature and pH of the environmental media, natural photosensitizers, etc., antibiotic drugs are prone to hydrolysis or photolysis [49]. One probable reason why antibiotic residues were not detected in the environmental media is that they had been Our previous studies [46,47] have shown that sulfonamides and β-lactams antibiotic residues were not detected in Min-xin river water and soil along the river [48]. This is likely due to that antibiotic drugs can be degraded in the environment.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…With the influence of temperature and pH of the environmental media, natural photosensitizers, etc., antibiotic drugs are prone to hydrolysis or photolysis [49]. One probable reason why antibiotic residues were not detected in the environmental media is that they had been Our previous studies [46,47] have shown that sulfonamides and β-lactams antibiotic residues were not detected in Min-xin river water and soil along the river [48]. This is likely due to that antibiotic drugs can be degraded in the environment.…”
Section: Discussionmentioning
confidence: 99%
“…Our previous studies [ 46 , 47 ] have shown that sulfonamides and β-lactams antibiotic residues were not detected in Min-xin river water and soil along the river [ 48 ]. This is likely due to that antibiotic drugs can be degraded in the environment.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This dictates the need for its simultaneous determination with other members of this class. The techniques of HPLC liquid chromatography [5], thin layer chromatography [5], capillary electrochromatography [6], electrophoresis [7,8], and spectrophotometry [9] are used for the determination of 4-aminobenzenesulfonic acid derivatives. For the analysis of media with complex matrixes, including those containing several 4-aminobenzenesulfonic acid derivatives, hybrid methods combining extraction and chromatography with tandem mass-spectrometric [10][11][12] Polymers 2022, 14, 2545 2 of 21 or UV-detectors [13], extraction and electrophoresis with UV-detection [14], extraction and UV-Visible spectrometry [15,16] are commonly used.…”
Section: Introductionmentioning
confidence: 99%
“…Sulfonamides (SAs) are a kind of artificial synthetic antibiotics, which are mainly used to effectively prevent and treat various infectious diseases in human and animals. However, the excessive or long-term use of SAs will lead to their wide spread emission in the environment, which will increase the resistance of aquatic microorganisms and then affect the human body through the food chain. , For example, causing the body flora imbalance, digestive system dysfunction, and even death. , This seriously threatens human health and the ecosystem. At present, the removal of antibiotics has become a worldwide environmental health problem.…”
Section: Introductionmentioning
confidence: 99%